Pemanfaatan Aplikasi Telegram Sebagai Platform Bisnis Digital : Perspektif Pelajar Sebagai Pengguna Aktif Telegram - Listari Noviyanti (Jurnal Bisnis Kreatif dan Inovatif, 2024)
Nowadays, advances in information and communication technology have opened up new opportunities in the world of digital business, including the use of the Telegram application as a business platform. This research aims to understand how students, as the digital native generation and active users of Telegram, utilize this application to carry out digital business activities. The author conducted the research using a descriptive qualitative approach, and collected data through interviews, observations, and library studies involving six informants aged 14-17 years. The results of this study show that the Telegram App, with features such as channels, large-capacity groups, and automated bots, provides flexibility and efficiency that support students in running small businesses, such as selling services, digital products, and community management. However, challenges such as fraud risk and fierce competition are also major obstacles. This research highlights the potential of Telegram in supporting students to develop creativity, communication skills and entrepreneurial spirit early on, while contributing to economic empowerment in the digital era.